ISSR based analysis of genetic variability of plantlets culture of pineapple (Ananas comosus L.) from Sipahutar, North Sumatera, Indonesia - Fauziyah Harahap; Annisa Afiva; Miftahul Jannah; Eko Prasetya (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Sipahutar pineapple is very popular in North Sumatra, because of the distinctive sweet taste and normal water content. Furthermore, it is large in size and has a yellow fruit skin color with greenish tips. However, the problem with Sipahutar pineapple production is the limited amount of good quality seeds. The utilization of in vitro culture techniques on pineapples allows the emergence of somaclonal variations, especially in plantlets that have undergone the subculture stage. This somaclonal variation is one of the problems in commercial seedling production, therefore, it is necessary to conduct an initial examination using the inter simple sequence repeat (ISSR) molecular marker. This study aimed to determine the genetic and primary stability of ISSR, which can be used in pineapple plants native to Sipahutar. The methods used include sample preparation, DNA isolation, primer optimization, ISSR primer amplification by PCR method, and electrophoresis. Furthermore, a total of 15 samples were amplified with six ISSR primers, and the data were analyzed by cluster method using the NTSYS-PC software. The final result was visualized in a dendrogram and analysis of diversity was conducted using GenAlex. The results showed that the level of genetic variability of the Sipahutar pineapple, which has undergone in vitro culture using six ISSR molecular markers was 76-97%. Meanwhile, the genetic variability level of the native to Sipahutar pineapple can be influenced by the long culture period and the use of N6-benzyladenine. The primers can be used to observe the genetic variability, except for ISSR 25 with a PIC value of 0.000.